Development of Online Web Learning with Ethnomatematics Content on Self Regulated Learning - Wikan Budi Utami; Dedi Kuswandi; Yerry Soepriyanto; Fikri Aulia (JTP - Jurnal Teknologi Pendidikan, 2023)
Along with the development of technology, a set of abilities is needed to master the 21st-century skills which are often referred to as 4C, namely Critical Thinking, Communication, Collaboration, and Creativity and Innovation. The purpose of this research is to develop online web learning with ethnomathematics content on self-regulated learning. The development model in this research is to develop online web learning with ethnomathematics content on KPK and FPB material for elementary schools with the Lee and Owen model design (2004). The development model consists of (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. After discussing the findings, this study produces several conclusions. First, in order to achieve learning outcomes and learning objectives, content from the etomathematics aspect is needed in the KPK and FPB materials so that students do not only get mathematics but understand how elements of local culture can foster a love for local culture. Second, to foster student interest, it requires the use of images, audio and video more than text. Third, applications can be used to support learning. This is due to the limited time that the researcher has. In the future, products that have been made large group trials and tests on student self-regulated learning.